Respon Viabilitas Benih Padi (Oryza sativa L.) pada Perendaman Air Kelapa Muda - Noor Aisyah; Jumar Jumar; Tuti Heiriyani (Agroekotek View, 2020)
Rice seeds are food crops whose demand continues to increase with increasing population in Indonesia. To increase rice productivity is to plant quality seeds of rice. Quality seeds also have problems if they have a long storage, so efforts are needed to improve quality by soaking before planting. This immersion can be done using young coconut water.This research aims to to determine the effect of young coconut water on the viability of rice seeds and knowing the best concentration of young coconut water on the viability of rice seeds. Completely Randomized Design one factor was used with different concentrations of young coconut water: K0(-)=without soaking,  K0(+)=KNO3 3%, K1=30%, K2=50%, and K3=70%. Each treatments obtained with 4 replications, so there were 20 experimental units. The result showed that the treatments with young coconut water on viability of rice seeds significantly affects on the percentation of seeds germination and unison growth of seeds. Treatment with 30% young coconut water significantly affects on percentation of seeds germination at 88,50% and 44% on unison growth of seeds